Noise characteristics of semiconductor lasers with narrow linewidth - Hua Wang; Yuxin Lei; Qiang Cui; Siqi Li; Xin Song; Yongyi Chen; Lei Liang; Peng Jia; Cheng Qiu; Yue Song; Yubing Wang; Yiran Hu; et al. (Heliyon)
Narrow-linewidth semiconductor lasers are highly valued in scientific research and industrial applications owing to their high coherence and low phase noise characteristics, particularly in high-performance optical communications, sensing, and microwave photonic systems. Accuracy, a key objective of many application systems, is determined by the noise of the light source. As system accuracy improves, the requirements for the light source become more stringent, with linewidth reduction and noise reduction being the top priorities. Currently, extensive attention and research are focused on suppressing noise generated by narrow-linewidth lasers. This paper presents noise measurement methods, analyses of the mechanisms for noise suppression, and recent research progress in low-noise semiconductor lasers, focusing on material optimization, structural design, and feedback control. The limitations of current technological solutions are discussed, and future scientific trends are outlined.